Prediction of thermal behavior of trickle bed reactors: The effect of the pellet shape and size - Taulamet, María José (2017)
Heat transfer plays an important role in several applications of packed bed reactors with cocurrent downflow of liquid and gas (widely known as trickle-bed reactor – TBR). A literature survey shows that the amount of articles dealing with the prediction of heat transfer rates between a TBR and an external heating or cooling source is limited for spherical catalyst pellets and definitively scarce for other pellet shapes as cylinders and multilobes. Results from an experimental program devoted to study heat transfer between a TBR and an external jacket, employing spherical and cylindrical particles and a commercial trilobe pellet, are presented. A wide range of gas (air) and liquid (water) flow rates were covered corresponding to low and high interaction regime. A two dimensional pseudohomogeneous model was employed to represent the thermal behavior of the packed bed. Values of the effective radial thermal conductivity and the wall heat transfer coefficient were obtained by regression of radial temperature profiles for three different bed lengths. Finally, expressions to estimate both parameters for the different particle shapes were developed, thus providing a useful predictive tool, not available in the literature up to the best of our knowledge.